Establishment and development of higher education: state, challenges, prospects (Economics and region, 2022)
The paper studies the current state, challenges, prospects for the formation and development of higher education. It was established that the infrastructure of military defenses suffered a differentiated level of damage and destruction as a result of intense shelling and bombing, 5 military defenses were completely destroyed, and 41 military defenses were damaged (approximately 11% of all military defenses in Ukraine). It was determined that 34 higher education institutions from Luhansk, Donetsk and AR Crimea, Mariupol, Kramatorsk, Slovyansk, Kherson, Sumy, etc. are in the process of relocation. It has been found that the monetary damages caused to the educational sector as a result of partial or complete destruction of buildings amount to 3.52 billion dollars. the USA, and the most total damage was caused to Kharkiv and Donetsk regions (47.2%). It was determined that the main challenges facing the educational sphere of Ukraine are infrastructural challenges, significant limitations in financing the education system, the outflow of Ukrainian and foreign students from higher education institutions, the inability to ensure academic integrity in higher education institutions under martial law, the need to update educational programs to modern requirements . It was established that the main task for the Ministry of Education and Science of Ukraine was the development and implementation of the formed practical recommendations regarding the organization of the educational process in the conditions of martial law. The methods of organizing the educational process in the conditions of martial law are defined. A model of providing educational services of higher education institutions under martial law conditions has been formed. The criteria that must be observed in order to maintain the effectiveness of distance learning in higher education institutions during the martial law in Ukraine are highlighted. Issues that need to be resolved immediately in the near future in the field of education are identified, namely systemic limitations (lack of prerequisites for long-term planning and forecasting in the field of education due to military operations on the territory of Ukraine; morally and technically outdated research infrastructure, etc.); staffing restrictions (insufficient staffing of the Military Academy, as a result of military operations and evacuation); financial limitations (imperfectness of current instruments of competitive financing of science and grant support of scientific research).
Keywords: challenges; prospects; higher education